A study on management of type 2 diabetic patients with complications - Brahmbhatt, Shruti Vihang; Sattigeri, Bhagya M. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Diabetes is a major public health problem both in developing and non-developing countries across the world. It is a chronic disease, which in long term causes several complications resulting in poly pharmacy for its management. Hence, this study was determined to analyze the drug utilization pattern for the management of type 2 diabetes with complications. Methods: A prospective, observational and non-interventional study was carried out in 100 diabetic patients with one or other complications admitted in medicine wards at Dhiraj Hospital. Patients who signed informed consent form were only included in the study. All the data were recorded from patients’ case files and analyzed. Results: Result of total 100 patients, maximum number 52 (52%) were falling in group of 61-70 kg and only 2 (2%) in 81-90 kg. Out of 100 diabetic patients, 40 (40%) were managed with insulin in addition to oral antidiabetic agents, 37 (37%) were managed with only Oral Hypoglycemic Agents (OHA) and 23 (23%) were managed with only insulin. The most commonly prescribed oral antidiabetic group of drug was Biguanides in 60 (60%) and most prescribed insulin was short acting Insulin in 40 (40%) patients. Conclusions: The diabetic patients are more prone to cardiovascular and other complications leading to a co morbid condition. The poly pharmacy is likely to occur in diabetic patients suffering with secondary complications. Therefore, intense blood sugar control with proper education can prevent the co morbid state and finally helps in reducing the economic burden.